PENYELENGGARAAN ABSENSI BERBASIS ELEKTRONIK: (Studi Pada Badan Kesatuan Bangsa Dan Politik Kota Manado) - Gisella Ruauw; Goinpeace H. Tumbel; Monika Kawahe; Elvis Lumingkewas (Post Graduate School of Government Science, 2023)
The National Unity and Political Agency of Manado City has implemented electronic attendance with facial recognition. However, there are still many employees who are late in filling in absences and are not effective in carrying out the work as assigned. The aim of this research is to analyze the use of electronic-based attendance at the Manado City National and Political Unity Agency. The type of method used in this research is qualitative descriptive research using data collection techniques, namely: observation, interviews and documentation. The results of the research show that the use of electronic-based attendance at the National Unity and Political Agency can improve employee discipline, seen from work discipline which is revealed as a crucial aspect in improving overall human resource performance involving individual awareness and willingness to comply with social rules and norms, so that A holistic approach is needed in developing work discipline. The human resources dimension highlights the need for better understanding regarding technological developments, especially in the implementation of Electronic-Based Attendance. In the optimal supervision dimension, it can be guaranteed by direct and effective monitoring from the leadership, so that employee responsibility and work results can be improved. Supervision as monitoring and also as a process of analysis and adjustment aimed at achieving organizational efficiency and effectiveness